The use of bromothymol blue and sodium thiopentone to confirm tracheal intubation. - John Dingley (Anaesthesia, 1996)
The possibility of using chemical changes to confirm correct tracheal tube placement was investigated with a view to their use in developing countries where more sophisticated methods are unavailable. The effect of bubbling expired gases through a 10% solution of bromothymol blue and a 0.25% solution of thiopentone led to chemical changes producing, in the case of bromothymol blue, a colour change and in that of thiopentone, precipitation, probably due to a change in pH caused by carbon dioxide. We also discovered that the time to precipitation of the thiopentone could be greatly reduced if it was mixed with a precise quantity of lignocaine. These simple end points can reliably confirm the correct placement of a tracheal tube at least as rapidly as the correct use of capnography.